Boosting the Potential of Chemotherapy in Advanced Breast Cancer Lung Metastasis via Micro‐Combinatorial Hydrogel Particles (Adv. Sci. 10/2023). Issue 10 (5th April 2023) - Palange, Anna Lisa; Mascolo, Daniele Di; Ferreira, Miguel; Gawne, Peter J.; Spanò, Raffaele; Felici, Alessia; Bono, Luca; Moore, Thomas Lee; Salerno, Marco; Armirotti, Andrea; Decuzzi, Paolo
Abstract : Drug Delivery The cover shows multiple metastatic nodules developing at different locations within the lungs. Deformable micro‐combinatorial hydrogel particles (μCGP) are transported by the blood flow, accumulate proximally to the nodules, and release in a sustained fashion thereof the therapeutic cargo—docetaxel nanomedicines. In an advanced triple negative breast cancer lung metastasis model, μCGP amplify the chemotherapy potential and boost animal survival beyond 5 months. More details can be found in article number 2205223 by Paolo Decuzzi and co‐workers.